Switzerland : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Switzerland. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Switzerland showed impressive growth performance owing to its strong macroeconomic policies and structural reform efforts. Executive Directors emphasized the need to maintain financial stability. They welcomed the well-timed injections of liquidity into the banking system. Directors also welcomed the stress testing framework to improve liquidity risk management, banks' contingency plans, and liquidity management policies. They commended the monetary policy stance and the strong fiscal performance. They welcomed the Long-Term Sustainability Report and also the extension of the debt-brake rule to incorporate expenditures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet